2021
DOI: 10.1016/j.nicl.2021.102643
|View full text |Cite
|
Sign up to set email alerts
|

Latent patterns of task-related functional connectivity in relation to regions of hyperactivation in individuals at risk of Alzheimer’s disease

Abstract: Highlights Hyperactivation relates to memory-related network dysfunction in SCD + and MCI. Hippocampal hyperactivation and connectivity relate to worst memory performance. In contrast, neocortical hyperactivation and connectivity may reflect compensation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Previous studies have shown hyperconnectivity in AD networks is associated with hyperactivity[9, 12, 22, 73]. To confirm if this is the case in hAPP mice, we compared functional connectivity, or correlated c-Fos + cell densities between brain regions, both within the visual network and across the brain.…”
Section: Resultsmentioning
confidence: 94%
“…Previous studies have shown hyperconnectivity in AD networks is associated with hyperactivity[9, 12, 22, 73]. To confirm if this is the case in hAPP mice, we compared functional connectivity, or correlated c-Fos + cell densities between brain regions, both within the visual network and across the brain.…”
Section: Resultsmentioning
confidence: 94%
“…For instance, well-established cognitive models suggest that the capacity of “binding” separate elements into a compound episode (Li et al, 2005), which can also be understood through the lens of context, would be selectively degraded in PAD (Della Sala et al, 2012; Parra et al, 2010). Studies leveraging experimental tasks assessing associative memory learning, which requires associating target items to contextual features, found lower performance in individuals with PAD compared to healthy controls (Berron et al, 2020; Clément & Belleville, 2012; Corriveau-Lecavalier et al, 2020, 2021; Polcher et al, 2017). Interestingly, some of these studies used functional Magnetic Resonance Imaging and observed that low associative memory performance was accompanied by hyperactivation of hippocampal and temporal areas, a well-documented early biomarker of AD (Corriveau-Lecavalier et al, 2020, 2021; Selkoe, 2019; Zott, 2019; Zott et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies leveraging experimental tasks assessing associative memory learning, which requires associating target items to contextual features, found lower performance in individuals with PAD compared to healthy controls (Berron et al, 2020; Clément & Belleville, 2012; Corriveau-Lecavalier et al, 2020, 2021; Polcher et al, 2017). Interestingly, some of these studies used functional Magnetic Resonance Imaging and observed that low associative memory performance was accompanied by hyperactivation of hippocampal and temporal areas, a well-documented early biomarker of AD (Corriveau-Lecavalier et al, 2020, 2021; Selkoe, 2019; Zott, 2019; Zott et al, 2018). Thus, although the network architecture presented in this study was not explicitly designed to reproduce biological learning systems, it is nonetheless consistent with knowledge highlighting the importance of context for efficient learning.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that during memory tasks, the activity of neurons in the medial temporal lobe or the hippocampus is greater in patients with early-stage mild cognitive impairment (MCI) than in healthy subjects, and that greater activation of neurons is associated with poorer performance ( Dickerson et al, 2004 ; Yassa et al, 2010 ; Corriveau-Lecavalier et al, 2021a ), indicating that such hyperactivation is detrimental to brain function. In fact, the drug levetiracetam ameliorates the lowered memory performance as well as hyperactive state in the hippocampus of MCI patients ( Bakker et al, 2012 , 2015 ).…”
Section: Excessive and Maladaptive Synaptic Plasticity With Agingmentioning
confidence: 99%
“…However, hippocampal hyperactivation during memory task is already detectable in healthy young APOE ε4 carriers who are unlikely to have Aβ deposition ( Filippini et al, 2009 ; Dennis et al, 2010 ). Besides, hyperactivation is task-dependent, implying that it is associated with altered patterns of functional connectivity ( Corriveau-Lecavalier et al, 2021a ). Although remodeling of the neuronal network compensates for loss of brain function which declines with aging, it has also become evident that plastic remodeling is sometimes detrimental.…”
Section: Excessive and Maladaptive Synaptic Plasticity With Agingmentioning
confidence: 99%